Mental health and disordered eating in athletes - Kussman, A.; Choo, H. J. (Clinics in Sports Medicine, 2024)
Disordered eating (DE) and eating disorders (EDs) are more prevalent in athletes than non-athletes, and can cause devastating health and performance consequences. Although they can affect any athlete, DE/EDs are more common among women and athletes in lean sports, where there is a perceived competitive advantage to being lean. The sports medicine provider plays a crucial role in screening, diagnosis, and treatment of DE/ED. Treatment should involve a multidisciplinary team with a physician, dietitian, and mental health provider. Preventative efforts should seek to educate athletes and their coaches/support staff and should foster a healthy environment, which deemphasizes weight or body image.